Penerapan Asas Kehati-hatian Notaris dalam Pembuatan Akta Perjanjian pada Kontrak Dagang sebagai Upaya Memberikan Kepastian Hukum bagi Para Pihak - Dian Cahayani (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Notaries play an important role in providing legal certainty through their authority to draw up authentic deeds, including deeds of agreement used in commercial contractual relationships. The complexity of commercial contracts and the differing interests of the parties require Notaries not only to comply with the formal requirements for drawing up deeds but also to act carefully, meticulously, impartially, and with due regard to the interests of the parties. This study aims to analyze the application of the principle of prudence by Notaries in drawing up deeds of agreement for commercial contracts and to examine its role in providing legal certainty for the parties. This study employs normative legal research using statutory and conceptual approaches. Legal materials are obtained through a literature review and analyzed using a qualitative descriptive method. The results indicate that the principle of prudence in drawing up deeds of agreement for commercial contracts is implemented through the identification and verification of the parties' identities and legal authority, examination of documents and the legal status of the contractual object, assessment of compliance with the legal requirements of an agreement, formulation of clear and balanced contractual clauses, and compliance with the formal requirements for authentic deeds. The application of this principle plays an important role in preventing legal defects, reducing potential disputes, preserving the evidentiary value of authentic deeds, and providing legal certainty regarding the rights and obligations of the parties. Therefore, the principle of prudence constitutes an essential aspect of the performance of a Notary's duties in producing deeds of agreement that are legally valid, enforceable, and capable of providing legal certainty in commercial contractual relationships.